Pulmonary mycoses among the clinically suspected cases of pulmonary tuberculosis - Bhutia, Tshering Ongmu; Adhikari, Luna (International Journal of Research in Medical Sciences, 2017)
Background:This study was carried with the main objectives: (1) to find out the occurrence of pulmonary mycoses in clinically suspected pulmonary tuberculosis cases at central referral hospital, Tadong, Sikkim. (2) To find out the various fungi causing pulmonary mycoses in clinically suspected pulmonary tuberculosis cases. Methods:200 clinically suspected pulmonary tuberculosis cases who visited the department of microbiology for the diagnostic microscopic examination of sputum sample for acid fast bacilli were included in this cross sectional study, carried out under the department of microbiology, Sikkim Manipal institute of medical sciences, over one year. Smears of sputum samples were examined microscopically for acid fast bacilli and fungal elements. Sputum samples were also plated onto different fungal culture media. Results:Out of 200 patients, various types of pathogens were detected in 54 (27%) patients. Fourteen (7%) patients were positive only for AFB, while fungus as a primary etiological agent was detected in 16(8%) patients. Fungus as a secondary etiological agent was detected in 4 (2%) patients [AFB with fungus in 2 (1%), AFB with fungus and bacteria in 1 (0.5%) and bacteria with fungus in 1 (0.5%) patient]. Conclusion:Pulmonary mycosis can be a primary infection in non- tuberculosis cases or co-infection in pulmonary tuberculosis cases. Investigation for fungal cause in clinically suspected cases of pulmonary tuberculosis will prevent misdiagnosis and mistreatment of cases.